PERBANDINGAN PERILAKU LENTUR BALOK NORMAL DAN BALOK BETON DENGAN PENAMBAHAN FLY ASH 10 % & 15 % - WAHYUDI, INDRA DIAN (KURVA S JURNAL MAHASISWA, 2017)
Normal concrete is concrete that has a weight of 2200 - 2500 kg / m3 using natural aggregates were broken or without broken. Concrete is the construction material that most common in use and in demand because as a basic material that easily formed with the relatively cheap price compared with the other construction.Mineral additive is added into the mix a lot of concrete with different goals, one of which could add to the strength of concrete. For that we need to know there is no research about it. This study used a mineral additive in the form of fly ash. To support the benefits of using alternative materials in the East Kalimantan province in the concrete mixture used material coming from the province of East Kalimantan, coarse aggregate of koral stone from Kaliorang and aggregate from the Mahakam river from the village of Loa Duri.Mix design or composition of the concrete mix using methods (Comparison 1: 2: 3) in the test material using a coarse stone aggregate maximum of 40 mm. Reinforcement concretewith Mahakam sand and cora as much as 6 sample, reinforcement concrete with added material of fly ash 10% as much as 6 sample, and reinforcement concrete with added material of fly ash 15% as much as 6 sample. As well as using the factors of age 14 and 28 days so the total sample of 36. From the test results flexural strength on the beam which uses a mixture and reinforcement at the age of 14 and 28 days above described acquired flexural strength to mix plain Mahakam sand and coral (fc): 19,111 kg / cm², a with added material of fly ash 10% (fc): 20,222 kg / cm², and a with added material of fly ash 15% (fc): 20,889 kg / cm².